A highly attenuated vaccinia virus strain LC16m8-based vaccine for severe fever with thrombocytopenia syndrome - Yoshikawa, Tomoki; Taniguchi, Satoshi; Kato, Hirofumi; Iwata-Yoshikawa, Naoko; Tani, Hideki; Kurosu, Takeshi; Fujii, Hikaru; Omura, Natsumi; Shibamura, Miho; Watanabe, Shumpei; Egawa, Kazutaka; Inagaki, Takuya; et al. (PLoS pathogens, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) caused by a species Dabie bandavirus (formerly SFTS virus [SFTSV]) is an emerging hemorrhagic infectious disease with a high case-fatality rate. One of the best strategies for preventing SFTS is to develop a vaccine, which is expected to induce both humoral and cellular immunity. We applied a highly attenuated but still immunogenic vaccinia virus strain LC16m8 (m8) as a recombinant vaccine for SFTS. Recombinant m8s expressing SFTSV nucleoprotein (m8-N), envelope glycoprotein precursor (m8-GPC), and both N and GPC (m8-N+GPC) in the infected cells were generated. Both m8-GPC- and m8-N+GPC-infected cells were confirmed to produce SFTSV-like-particles (VLP) in vitro , and the N was incorporated in the VLP produced by the infection of cells with m8-N+GPC. Specific antibodies to SFTSV were induced in mice inoculated with each of the recombinant m8s, and the mice were fully protected from lethal challenge with SFTSV at both 10 3 TCID 50 and 10 5 TCID 50 . In mice that had been immunized with vaccinia virus strain Lister in advance of m8-based SFTSV vaccine inoculation, protective immunity against the SFTSV challenge was also conferred. The pathological analysis revealed that mice immunized with m8-GPC or m8-N+GPC did not show any histopathological changes without any viral antigen-positive cells, whereas the control mice showed focal necrosis with inflammatory infiltration with SFTSV antigen-positive cells in tissues after SFTSV challenge. The passive serum transfer experiments revealed that sera collected from mice inoculated with m8-GPC or m8-N+GPC but not with m8-N conferred protective immunity against lethal SFTSV challenge in naïve mice. On the other hand, the depletion of CD8-positive cells in vivo did not abrogate the protective immunity conferred by m8-based SFTSV vaccines. Based on these results, the recombinant m8-GPC and m8-N+GPC were considered promising vaccine candidates for SFTS.